RETRACTED ARTICLE: Ethics, Autonomy and Learning: Progress of a case study (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2023)
This article was retracted. The retraction notice can be found here: https://doi.org/10.37819/revtechno.1990This paper presents the progress of an investigation that is being carried out in two higher education institutions in the city of Bogotá-Colombia. Part of the work carried out a search for studies that have been carried out based on three key concepts that are related in a systemic way: Ethics, Autonomy and Learning. The purpose of our project is to investigate the way in which students relate these concepts in their academic training processes. A mixed methodology is chosen, specifically, the QUANTI/cuali method, proposed by Hernández-Sampieri (2018), which he calls "dominant" because the quantitative perspective prevails.